(untitled) - 1981-; Gad, Josh; Dinklage, Peter; Cox, Brian; 1946-; (Henry Pryce); Kazan, Lainie; Jackman, Henry; Winborne, Hughes; Mokri, Amir; Monaghan, Michelle; James, Kevin; et al. (Culver City, California, 2015)
As kids in the 1980s, Sam Brenner, Will Cooper, Ludlow Lamonsoff, and Eddie "The Fire Blaster" Plant saved the world thousands of times, at 25 cents a game in the video arcades. Now, theyre going to have to do it for real. In Pixels, when intergalactic aliens discover video feeds of classic arcade games and misinterpret them as a declaration of war, they attack the Earth, using the video games as the models for their assaults.
Keywords: Drama; Video game characters; Video games; Video game characters; Video arcades; Video games; Drama; Human-alien encounters; Drama; Video game characters; Video arcades; Human-alien encounters; Drama; Drama; Science fiction films; Feature films; Feature films; Action and adventure films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Drama; Feature films; Comedy films; Action and adventure films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Fiction films; Comedy films; Science fiction films